Examination of the Mellitah Oil and Gas Complex's AISI 304 Stainless Steel Transmission Superheated Steam Pipeline: (Corrosion Failure) - Abdulsalam Salama; Mohammed Al-Madani; Salah Gnefid; Emhemed Madi; Abdul-Hamid Ibrahim (African Journal of Advanced Pure and Applied Sciences, 2024)
Since petrochemical companies frequently employ 304 stainless steel pipes, this study was carried out on the same kind of pipe to examine the early failure of the high-pressure steam coil used in the fuel exhaust unit at Mellitah Industrial Complex. This failure manifested as vapor leaking through the spool's exterior surface fissures, which were evident. The hardness test, X-ray examination, microscopic inspection, visual inspection, and chemical analysis were the most crucial tests carried out to assess the metallurgical failure. The surface of the stainless-steel pipe had pitting erosion, as seen by the microscopic investigation photographs, the presence of this corrosion was confirmed after grinding and smoothing the surface of the sample There is a good explanation why the ingot got damaged. Stress corrosion cracking (SCC) was discovered throughout the interior structure of the stainless-steel pipe, as shown by an X-ray inspection. The presence of the fractures was also visible in the microscopic photographs. By comparing the results of the chemical analysis as well as the hardness test obtained in this research with international specifications, it was found that they conform to them, and this refutes what was stated in the reports of the Mellitah oil and gas complex that the type of corrosion that occurs in the superheated steam transmission pipe is corrosion resulting from thermal fatigue.